Unicity theorems with truncated multiplicities of meromorphic mappings in several complex variables for few fixed targets - Pham, Hoang Ha; Si, Duc Quang (Ukrains’kyi Matematychnyi Zhurnal, 2019)
The purpose of our paper is twofold. Our first aim is to prove a uniqueness theorem for meromorphic mappings of C^n into P^N(C) sharing 2N + 2 hyperplanes in the general position with truncated multiplicities, where all common zeros with multiplicities more than a certain number do not need to be counted. Second, we consider the case of mappings sharing less than 2N + 2 hyperplanes. These results are improvements of some recent results.